Executive and Attentional Functions in Chronic Pain: Does Performance Decrease with Increasing Task Load? - Joukje M Oosterman; Laura C Derksen; Albert JM van Wijck; Roy PC Kessels; Dieuwke S Veldhuijzen (Pain Research and Management)
BACKGROUND: Diminished executive function and attentional control has been reported in chronic pain patients. However, the precise pattern of impairment in these aspects of cognition in chronic pain remains unclear. Moreover, a decline in psychomotor speed could potentially influence executive and attentional control performance in pain patients.